A case of atheroembolic renal disease: Not uncommon but underdiagnosed - chettipunyam Sounderajan, chetan; Venkatappa, Nandeesh (Indian Journal of Case Reports, 2026)
Atheroembolic renal disease (AERD) is the renal component of the more generalized cholesterol embolization syndrome (CES) that results from rupture of the cholesterol-rich plaques in the larger arteries. Most cases are iatrogenic following invasive intravascular procedures, and >25% occur spontaneously. Cholesterol emboli that lodge distally cause ischemia, inflammation, and end-organ damage. We report a 60-year-old male diabetic, hypertensive with cardiovascular problems, presenting with rapidly worsening renal failure following an angiogram. Renal biopsy confirmed AERD associated with inflammation. He showed a very good response to a course of steroids. AERD, though a common problem, remains largely underdiagnosed. Recent years have seen a rise in the incidence, probably due to an increase in the atherosclerosis risk factors and more patients undergoing invasive intravascular procedures. A high index of suspicion is needed for timely diagnosis, as some of them show a good response to steroids.